Trading strategies and trading profits in experimental asset markets with cumulative information - Thomas Stöckl; Michael Kirchler (University of Innsbruck, Department of Public Finance, 2010)
We study the use of trading strategies and their profitability in experimental asset markets with asymmetrically informed traders. We find that insiders make most of their profits from trades which are initiated by their limit orders especially at the beginning of a period and when the change in their fundamental information is large. The average informed lose most with market orders and their losses are highest at the beginning of a period when they can be exploited by insiders. Uninformed traders act as liquidity providers. They place the highest number of limit orders and end up with the market return.
Keywords: G12; G14; D03; 330; Asymmetric information; liquidity; trading strategies; limit order markets; experiment; Anlageverhalten; Asymmetrische Information; Börsenumsatz; Insiderhandel; Test